Mapping Solanum berthaultii-based late blight (Phytophthora infestans) resistance in a diploid population - Manrique, N.; Islam, M.; Enciso-Rodriguez, F.; Rosenzweig, N.; Coombs, J.; Douches, D. (Springer, 2020)
Late blight, caused by the oomycete Phytophthora infestans (Mont) de Bary, is the most important disease of cultivated potato (Solanum tuberosum L.). An efficient long-term strategy for controlling late blight infection involves integration of host plant resistance to disease management programs. In this study, a diploid potato population segregating for late blight resistance was generated from an interspecific cross (MSX902) between S. tuberosum x S. chacoense hybrid (84SD22) and a late blight resistant Solanum berthaultii hybrid (Ber83). A total of 129 progeny and two parents were tested for foliar resistance against the US-23 P. infestans genotype using detached-leaf bioassays and inoculated field trials (2014 and 2015). Distribution of foliar late blight resistance and susceptibility was bimodal in both types of phenotype evaluation, suggesting a major R-gene may be associated with the resistance. A major QTL for late blight resistance on chromosome 10 was detected using both detached leaf bioassay and field trial data. The SNP marker solcap_snp_c1_15219 (26.5 cM) was at the peak of the QTL. Additionally, a minor QTL on chromosomes 5 was linked to SNPs solcap_snp_c1_3793. These SNP markers closely linked to the late blight resistance QTL can be used for marker-assisted breeding.